A Contingency Approach to Strategy Implementation at the Business-Unit Level: Integrating Administrative Mechanisms with Strategy - Govindarajan, Vijay (Academy of Management Journal, 1988)
This study focused on what is perhaps the most critical aspect of strategy implementation in large, multibusiness organizations: recognizing that different business units within the same corporation often pursue different strategies and that the administrative mechanisms that corporate headquarters use to manage those businesses should differ. This study compared the results of bivariate and systems approaches to fit. Implications of the results for theory development and managerial practice are discussed.